89 Implementation of a Modified Version of Nice Clinical Guideline 95 On Chest Pain of Recent Onset: Experience in a District General Hospital. (3rd June 2016) - Green, Peregrine; Jordan, Stephanie; Ormerod, Julian; Haynes, Douglas; Harries, Iwan; Ramcharitar, Steve; Foley, Paul; McCrea, William; Beale, Andy; Chandrasekaran, Badri; Barnes, Edward
Abstract : Introduction: NICE Clinical Guidance 95 was introduced to Rapid Access Chest Pain Clinics (RACPC) to aid investigation of possible stable angina based on pre-test probability of coronary artery disease (CAD). Following a recent 6 month audit of its implementation in our centre, we introduced a modified version, such that all patients with low or moderate risk of CAD were referred for computated tomography coronary angiography (CTCA), whilst those at high or very high risk were referred for invasive angiography. Methods: The electronic patient records of 546 patients consecutively referred to our RACPC from primary care over a 6 month period were retrospectively analysed. Initial pre-test probability of CAD, referral for initial investigation, incidence of significant CAD and rates of revascularisation at a minimum follow-up time of 6 months were documented. Results: A large proportion of patients assessed had symptoms that were unlikely to be anginal in origin and were discharged directly from RACPC without further investigation. Rates of CAD generally correlated well with pre-test probability. Moderate risk patients showed low rates of CAD and revascularisation. CTCA had a shorter time to investigation than stresse cho, but a number of false positive results. High and very high risk patients had high rates of revascularisation and a large proportion of this was for prognostically significant disease. Conclusions: Low rates of CAD in low and moderate risk groups justifies the use of CTCA as a first line investigation in these patients, reducing waiting times to investigation. Routine investigation of very high risk patients allows a significant proportion to undergo revascularisation for prognostically significant disease. Strict adherence to NICE CG95 could possibly lead to these patients being missed.